Movimientos sociales y dictadura militar La experiencia política del Paro Nacional del 19 de julio de 1977 * - Valladares Quijano, Manuel (2007)
The present work summarises the development of the major movements with the direct interviention of the working class and of the social masses that took place throughout several weeks in Lima and provinces, and concluded in the extraordinary National Strike of 19 July 1977, against the ‘second phase’ of the military dictatorship; in fact the political trends of the working movement leadership are broadly approached, and the trends among grassroots movements.